2015
DOI: 10.1016/j.jclinepi.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate use and regulation of interventions against publication bias decreases their effectiveness: a systematic review

Abstract: ObjectivesTo determine the effectiveness of interventions designed to prevent or reduce publication and related biases.Study Design and SettingWe searched multiple databases and performed manual searches using terms related to publication bias and known interventions against publication bias. We dually reviewed citations and assessed risk of bias. We synthesized results by intervention and outcomes measured and graded the quality of the evidence (QoE).ResultsWe located 38 eligible studies. The use of prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 73 publications
1
22
0
2
Order By: Relevance
“…Yet, being aware of publication and related biases, there are many cases where these mechanisms have failed as filters. [23,24] This failure of the peer review system as information filter is one of the elements making external appraisal necessary.…”
Section: The Patients -General-purpose Information Filteringmentioning
confidence: 99%
“…Yet, being aware of publication and related biases, there are many cases where these mechanisms have failed as filters. [23,24] This failure of the peer review system as information filter is one of the elements making external appraisal necessary.…”
Section: The Patients -General-purpose Information Filteringmentioning
confidence: 99%
“…As part of the work conducted on research ethics committees, journal editors and publishers, and researchers Strech et aland Panteli, it was found that most of these stakeholders acknowledge the deleterious effects of dissemination bias on health care research but are unwilling or unable to implement measures to control the problem. In addition, a recent systematic review concluded that while implementation of measures to reduce dissemination bias is on the rise, they are not adequately conducted …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent systematic review concluded that while implementation of measures to reduce dissemination bias is on the rise, they are not adequately conducted. 36 Among surveyed agencies, there was wide support for making should not be limited to experimental trials but also to observational studies. However, these agencies appear to be taking little or no action to implement these measures.…”
mentioning
confidence: 99%
“…Pese a lo dicho, un estudio retrospectivo realizado en ocho revistas médicas, observó que ninguno de dichos aspectos había influenciado (aparentemente) en la decisión editorial, indicando que también existe un creciente interés por parte de las revistas en realizar un manejo ético y que minimice el sesgo de publicación 12 . Para minimizar el sesgo de publicación se han delineado varias opciones que incluyen desde la aplicación de modelos estadísticos en la evaluación de las evidencias, hasta la creación de estrategias de información y comunicación de su importancia o la elaboración de políticas de transparencia sobre el desarrollo y la publicación de investigación 7,13 . En los últimos años, quizás gracias a la campaña #AllTrials (http://www.alltrials.net/), el registro y publicación de protocolos ha adquirido un creciente interés y relevancia en la intención de minimizar el sesgo de publicación y evitar la modificación de protocolos una vez iniciada la investigación 14 .…”
Section: E D I T O R I a Lunclassified